Features of the Clinical Course of Enterobiasis in Children (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Parasitic diseases constitute a significant part of infectious pathology, including in children. However, the massive spread of parasitic diseases is recorded in all regions of the world. The WHO expert assessment indicates that in terms of the number of patients, helminthiases are in 3rd place in the world, and malaria is in 4th place among all the most significant infectious and parasitic diseases.